Digital literacy and religious moderation - Muhammad Eko Arief Wijaksono; Achmad Jasuli Afandi; Moh. Affan; Zarkoni; Ahmad Syauqi Alaikar Rohman; Hasbullah; Madlubur Rhisky (Lembaga Penerbitan, Penelitian dan Pengabdian kepada Masyarakat, Institut Badri Mashduqi, 2026)
This study aims to analyze students' digital literacy practices, the role of teachers in integrating digital literacy into learning, and the pedagogical construction of a synthesis between digital literacy and religious moderation values ​​in madrasas. This study uses a qualitative approach with a case study design conducted at SMAN 01 Tiris Probolinggo. Data collection techniques were carried out through in-depth interviews, participant observation, and documentation. Data analysis used an interactive model that includes data condensation, data reduction, data display, and conclusion drawing, with validity tests through triangulation of sources, techniques, and member checking. The results of the study show three main findings. First, students' digital literacy practices contribute to shaping their understanding of religious moderation through the ability to access, select, and critically evaluate religious information. Second, teachers have a strategic role as facilitators and epistemological filters in integrating digital literacy into learning. Third, the synthesis between digital literacy and religious moderation values ​​can be constructed pedagogically through the stages of digital information exploration, critical reflection, and internalization of values. This research confirms that digital literacy is not neutral, but rather requires values-based pedagogical interventions to foster moderate, inclusive, and contextual religious understanding. Theoretically, this research contributes to the development of an integrative model based on thesis-antithesis-synthesis dialectics in Islamic education. Practically, this research has implications for educational institutions to strengthen teacher capacity, develop digital literacy policies, and create a learning ecosystem that supports religious moderation in the digital era.